BOOK REVIEW: Daniel Ciurel, “Eminescu orator. Strategii retorice în publicistică” [“Eminescu the orator. Rhetorical strategies in journalistic articles”], Tritonic Publishing House, 2019, 308 p. - CERNICOVA, Mariana (Studia Universitatis Babeș-Bolyai Ephemerides, 2020)
Mihai Eminescu, the Romanian national poet, an emblematic figure for Romanian culture, was also a prolific publicist and newspaper editor. The reception and critical interpretation of his journalistic work was delayed largely because a full collection of his articles appeared in volumes only in 1989, at the centennial of his death. Eminescu is presented as one of the godfathers of the modern Romanian language, his exquisite style and the mastering of rhetorical devices consecrating him as a leading cultural figure in the 19th century. Most analyses are tribute to literary history, limited to thematic descriptivism, or repertoires of the economic, legal, political, or sociological ideas tackled by Eminescu in his articles. As a journalist, he was passionate and polemical, rooted in the specific socio-historical context of his time, features that hindered the critical reception of his journalistic activity during the troubled 20th century, marked by a succession of imposed ideological filters for the discussion of all issues concerning political, social, economic, or cultural topics not only in Romania, but throughout Eastern and Central Europe.